1999
DOI: 10.1080/073993399245584
|View full text |Cite
|
Sign up to set email alerts
|

Measures of American Indian Traditionality and its Relationship to Cervical Cancer Screening

Abstract: The goal of this study was to evaluate the relationship between culture and attitudes about cervical cancer screening among young American Indian women living and working in northeast Oklahoma. A cohort of 199 American Indian women, ages 18-40, were surveyed to determine their blood quantum, self-identification, and beliefs and practices regarding traditional behavior in order to develop a traditional behavior scale (the degree to which an individual maintained traditional tribal ways or behaviors). The use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 3 publications
0
11
1
Order By: Relevance
“…11 Others have found similar inverse relationships between measures of traditionalism and cancer screening. 45, 46 …”
Section: Discussionmentioning
confidence: 99%
“…11 Others have found similar inverse relationships between measures of traditionalism and cancer screening. 45, 46 …”
Section: Discussionmentioning
confidence: 99%
“…We found it culturally unacceptable to assess certain constructs such as trauma, just as Smith et al (2004) were not able to assess women’s personal sexual behavior as a risk factor for cervical cancer. We found that the issue of taboo topics of discussion arose with respect to suicide as in prior studies (Solomon & Gottlieb, 1999), and that the acculturation level of adolescents was a potential factor in the acceptability of certain ways of asking questions (Legaspi and Orr, 2007). Thus, the present measurement development process reflects many issues raised in prior reports of community intervention in American Indian/Alaska Native communities.…”
Section: Resultsmentioning
confidence: 65%
“…Several papers describe the host of cultural issues involved in adapting and creating measures in diverse cultural contexts. For example, the decision to use self-administered questionnaires rather than interviews was explored by Solomon and Gottlieb (1999). Their pilot test of the two formats resulted in no substantive differences in the information obtained.…”
Section: Culture and Technical Issues In Measure Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Several studies examining breast and cervical cancer screening among American Indian women foreground cultural characteristics, including Native language use, to explain screening disparities, but with mixed results. 1820 One population-based study of women on the Hopi reservation found a positive relationship between “traditionalism”—assessed as Native language use, Native cultural participation, and length of resevation residency—and protective health behaviors. 19 A study of almost 1,000 Lumbees in North Carolina—a tribe that has not retained a Native language—nevertheless found better knowledge of cervical cancer screening among women who identified more strongly with other aspects of their Native American culture.…”
Section: Introductionmentioning
confidence: 99%